Puccini's MADAMA BUTTERFLY (Opera Journeys Libretto Series) - Fisher, Burton D.; Fisher, Burton D (Opera Journeys Publishing, 2006)
A newly translated LIBRETTO of Puccini's MADAMA BUTTERFLY with many music examples.
Keywords: Operas -- Librettos; Operas; Puccini, Giacomo, 1858-1924. Madama Butterfly